Technical wildness: reforestation, rewilding, and the environmental performativity of forest measurement in the Scottish Highlands - Stanley, T (2024)

(untitled)
This thesis examines the ecological politics of reforestation in the Scottish Highlands, the large, sparsely populated expanse of mountains and moorland covering the north-western third of Scotland. The region has long been considered one of the UK’s last ‘wild’ places and, somewhat paradoxically, is increasingly framed as an ecologically degraded space ready to restore. The shared concern for reforesting Scotland brings together a range of epistemic groups, with varying commitments to generate profit, sequester carbon, and restore ecological processes. Stakeholders including private companies, research scientists, field ecologists, and state agencies are developing new models, metrics, and technologies to measure reforestation and create data which shows the ‘nature-based solutions’ forests deliver.